Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/openhrt-2015-000371
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive versus invasive management in patients with prior coronary artery bypass surgery with a non-ST segment elevation acute coronary syndrome: study design of the pilot randomised controlled trial and registry (CABG-ACS)

Abstract: IntroductionThere is an evidence gap about how to best treat patients with prior coronary artery bypass grafts (CABGs) presenting with non-ST segment elevation acute coronary syndromes (NSTE-ACS) because historically, these patients were excluded from pivotal randomised trials. We aim to undertake a pilot trial of routine non-invasive management versus routine invasive management in patients with NSTE-ACS with prior CABG and optimal medical therapy during routine clinical care. Our trial is a proof-of-concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…The design of this pilot trial has been previously described. 12 The participants were enrolled in 4 acute hospitals in the National Health Service (NHS), United Kingdom, including 2 large urban hospitals (Western Infirmary and Royal Infirmary, Glasgow) and 2 regional hospitals (Royal Alexandra Hospital, Paisley and Royal Blackburn Hospital). More details about these hospitals are detailed in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…The design of this pilot trial has been previously described. 12 The participants were enrolled in 4 acute hospitals in the National Health Service (NHS), United Kingdom, including 2 large urban hospitals (Western Infirmary and Royal Infirmary, Glasgow) and 2 regional hospitals (Royal Alexandra Hospital, Paisley and Royal Blackburn Hospital). More details about these hospitals are detailed in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Patients with prior CABG have been excluded from many important clinical trials including VINO 32 and RITA3 24,[33][34][35][36] and only contributed to small numbers of patients in other ACS clinical trials (in OASIS-5: 1643 of 20,078 patients, in LIPSIA-NSTEMI: 41 of 600 patients, in Italian elderly ACS: 29 of 313, and in After Eighty Study: 76 of 457 patients). [37][38][39][40][41][42] Apart from a recently published pilot study where Lee et al 43 reported 12-month outcome data from 60 prior-CABG patients (invasive group, n¼31; medical group, n¼29), no major clinical trials exclusively examined clinical outcomes of an invasive versus medical approach in patients who presented with acute MI and had prior CABG. 40 In our study, only half of prior CABG patients underwent invasive coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42] Apart from a recently published pilot study where Lee et al 43 reported 12-month outcome data from 60 prior-CABG patients (invasive group, n¼31; medical group, n¼29), no major clinical trials exclusively examined clinical outcomes of an invasive versus medical approach in patients who presented with acute MI and had prior CABG. 40 In our study, only half of prior CABG patients underwent invasive coronary angiography. There are many logistic and clinical factors which affect the selection of a management approach for prior-CABG patients presenting with acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, patients who were ineligible for randomisation and who gave informed consent were entered into an observational registry. The study design, 20 and results of the main trial have been published. 21 …”
Section: Methodsmentioning
confidence: 99%